The Effect of Career Development and Emotional Intelligence on Organizational Citizenship Behavior Mediated Job Satisfaction in Employees PDAM Tirta Deli - M. Topan Sahroni; R. Sabrina; Muis Fauzi Rambe (IHSA Institute, 2022)
The purpose of this study was to determine and analyze the effect of career development and emotional intelligence on organizational citizenship behavior mediated by job satisfaction. The sample in this study used a saturated sample, where all of the population was sampled, but employees as leaders and researchers were not included in the sample. The sample in this study amounted to 67 employees. The data collection technique in this study used a questionnaire method, with SEM-PLS statistical analysis. Data processing in this study using the software program SmartPLS 3.3.3. The results of this study prove that career development directly has a positive and significant effect on organizational citizenship behavior. Furthermore, emotional intelligence has a positive and significant effect on organizational citizenship behavior. While job satisfaction has a positive and significant effect on organizational citizenship, and career development has a positive and significant effect on job satisfaction, emotional intelligence has a positive and significant effect on job satisfaction, so indirectly job satisfaction can mediate career development on organizational citizenship behavior. And indirectly job satisfaction can mediate the influence of emotional intelligence on the organizational citizenship behavior of employees.